ANALYSIS OF THE IMPACT OF DIVIDEND POLICY ON COMPANY VALUE: A CASE STUDY ON MANUFACTURING COMPANIES LISTED ON THE IDX(Indonesia Stock Exchange) - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study aims to analyze the impact of dividend policy on company value among manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research method employed was a literature review, seeking references related to the research context under study. The findings indicate that the dividend payout ratio and dividend yield have a significant positive effect on company value, while dividend growth does not show a significant impact. These findings underscore the importance of dividend policy as a factor influencing investor perceptions of company value. The managerial implication of this research is that manufacturing companies on the IDX need to consider appropriate dividend strategies as part of their financial policies to enhance company value. This study also contributes to the financial literature by expanding understanding of the dynamics of dividend policy in the Indonesian capital market, particularly within the manufacturing sector.